The prevalence of intestinal parasites in orphanages in Yogyakarta - Suyoko Suyoko (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1980)
Stool specimens for microscopic examination collected from orphanages in Yogyakarta indicated the species and the overall percentages of prevalence of human intestinal parasites. These samples were examined in our laboratory by direct smear and concentration methods. The overall percentage of the sample population found infested with intestinal helminths was 43.4 and of intestinal protozoa was 39,8.KeyWords: intestinal helminths - intestinal protozoa - direct smear - Ritchie method - anal swab